Building it up.

Calculus Level 5

Let R 0 R_{0} and H 0 H_{0} be the radius and height of the initial right circular cone C 1 C_{1} . Find the volume V 1 V_{1} of the largest right circular cylinder with radius r 1 r_{1} and height h 1 h_{1} that can be inscribed in the initial cone C 1 C_{1} .

Now, let r 1 r_{1} and H 1 = H 0 h 1 H_{1} = H_{0} - h_{1} be the radius and height of the remaining right circular cone C 2 C_{2} . Find the volume V 2 V_{2} of the largest right circular cylinder with radius r 2 r_{2} and height h 2 h_{2} that can be inscribed in the remaining cone C 2 C_{2} .

In general for n 2 n \geq 2 : Let r n 1 r_{n - 1} and H n 1 = H n 2 h n 1 H_{n - 1} = H_{n - 2} - h_{n - 1} be the radius and height of the remaining right circular cone C n C_{n} . Find the volume V n V_{n} of the largest right circular cylinder with radius r n r_{n} and height h n h_{n} that can be inscribed in the remaining cone C n C_{n} .

Find V = n = 1 V n \displaystyle V = \sum_{n = 1}^{\infty} V_{n} and let V V^* be the total volume of the blue regions. If V cone V_{\text{cone}} is the volume of the initial right circular cone and V V cone = α β \dfrac{V^*}{V_{\text{cone}}} = \dfrac{\alpha}{\beta} , where α \alpha and β \beta are coprime positive integers, find α + β \alpha + \beta .


The answer is 26.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Aug 13, 2018

Since the answer we need is a ratio, for the ease of calculation, we can take H 0 = 1 H_0=1 and R 0 = 1 R_0=1 , therefore V cone = 1 2 π H 0 R 0 2 = π 3 V_{\text{cone}} = \dfrac 12 \pi H_0R_0^2 = \dfrac \pi 3 .

Considering r 1 r_1 and h 1 h_1 , due to similar triangles h 1 R 0 r 1 = H 0 R 0 \dfrac {h_1}{R_0-r_1} = \dfrac {H_0}{R_0} h 1 1 r 1 = 1 1 \implies \dfrac {h_1}{1-r_1} = \dfrac 11 h 1 = 1 r 1 \implies h_1 = 1-r_1 . Then the V 1 V_1 is given by:

V 1 = π r 1 2 h 1 = π r 1 2 ( 1 r 1 ) = π ( r 1 2 r 1 3 ) Differentiate both sides w.r.t. r 1 d V 1 d r 1 = π ( 2 r 1 3 r 1 2 ) and d 2 V 1 d r 1 2 = π ( 2 6 r 1 ) \begin{aligned} V_1 & = \pi r_1^2h_1 = \pi r_1^2 (1-r_1) = \pi (r_1^2-r_1^3) & \small \color{#3D99F6} \text{Differentiate both sides w.r.t. }r_1 \\ \frac {dV_1}{dr_1} & = \pi (2r_1-3r_1^2) & \small \color{#3D99F6} \text{and} \\ \frac {d^2V_1}{dr_1^2} & = \pi (2-6r_1) \end{aligned}

d V 1 d r 1 = 0 \implies \dfrac {dV_1}{dr_1} = 0 , when r 1 = 0 r_1=0 or r 1 = 2 3 r_1=\dfrac 23 . This means that V 1 V_1 is maximum when r 1 = 2 3 r_1=\dfrac 23 , since d 2 V 1 d r 1 2 r 1 = 2 3 < 0 \dfrac {d^2V_1}{dr_1^2} \bigg|_{r_1=\frac 23} < 0 .

Similarly, we have r 2 = 2 3 r 1 = ( 2 3 ) 2 r 0 r_2 = \dfrac 23 r_1 = \left(\dfrac 23\right)^2 r_0 , where r 0 = R 0 = 1 r_0=R_0=1 , r 3 = ( 2 3 ) n r 0 r_3 = \left(\dfrac 23\right)^n r_0 , r n = ( 2 3 ) n r 0 \implies r_n = \left(\dfrac 23\right)^n r_0 . Similarly, h n = r n 1 r n h_n = r_{n-1} - r_n . And V n = π r n 2 h n = π r n 2 ( r n 1 r n ) V_n = \pi r_n^2 h_n = \pi r_n^2 (r_{n-1}-r_n) . Therefore,

V = n = 1 V n = n = 1 π r n 2 ( r n 1 r n ) Since r n = ( 2 3 ) n = π n = 1 ( 2 3 ) 2 n ( ( 2 3 ) n 1 ( 2 3 ) n ) = π n = 1 ( 2 3 ) 3 n 1 ( 1 2 3 ) = π 2 n = 1 ( 8 27 ) n = π 2 8 27 ( 1 1 8 27 ) = 4 19 π \begin{aligned} V & = \sum_{n=1}^\infty V_n = \sum_{n=1}^\infty \pi r_n^2 \left(r_{n-1}-r_n\right) & \small \color{#3D99F6} \text{Since }r_n = \left(\frac 23\right)^n \\ & = \pi \sum_{n=1}^\infty \left(\frac 23\right)^{2n} \left(\left(\frac 23\right)^{n-1} - \left(\frac 23\right)^n\right) \\ & = \pi \sum_{n=1}^\infty \left(\frac 23\right)^{3n-1} \left(1 - \frac 23 \right) \\ & = \frac \pi 2 \sum_{n=1}^\infty \left(\frac 8{27}\right)^n \\ & = \frac \pi 2 \cdot \frac 8{27} \left(\frac 1{1-\frac 8{27}}\right) \\ & = \frac 4{19}\pi \end{aligned}

Therefore, V V cone = V cone V V cone = 1 V V cone = 1 4 19 1 3 = 1 12 19 = 7 19 \dfrac {V^*}{V_{\text{cone}}} = \dfrac {V_{\text{cone}}-V}{V_{\text{cone}}} = 1 - \dfrac {V}{V_{\text{cone}}} = 1 - \dfrac {\frac 4{19}}{\frac 13} = 1 - \dfrac {12}{19} = \dfrac 7{19} . Hence α + β = 7 + 19 = 26 \alpha + \beta = 7 + 19 = \boxed{26} .

Rocco Dalto
Aug 12, 2018

Let the volume of the cone V c o n e = 1 3 π R 0 2 H 0 V_{cone} = \dfrac{1}{3} \pi R_{0}^2 H_{0} and the volume of the cylinder V 1 = π r 1 2 h 1 . V_{1} = \pi r_{1}^2 h_{1}.

From the geometry of the problem we have two similar triangles whose proportion is: R 0 R 0 r 1 = H 0 h 1 \dfrac{R_{0}}{R_{0} - r-{1}} = \dfrac{H_{0}}{h_{1}} \implies

h 1 = H 0 ( R 0 r 1 ) R 0 V 1 = H 0 π R 0 ( R 0 r 1 2 r 1 3 ) h_{1} = \dfrac{H_{0}(R_{0} - r_{1})}{R_{0}} \implies V_{1} = \dfrac{H_{0} \pi}{R_{0}} * (R_{0}r_{1}^2 - r_{1}^3) \implies

d V 1 d r 1 = H 0 π R 0 r 1 ( 2 R 0 3 r 1 ) = 0 , r 1 0 r 1 = 2 R 0 3 . \dfrac{dV_{1}}{dr_{1}} = \dfrac{H_{0} \pi }{R_{0}} * r_{1} * (2R_{0} - 3r_{1}) = 0, r_{1} \neq 0 \implies r_{1} = \dfrac{2R_{0}}{3}.

d 2 V 1 d r 1 2 = H 0 π R 0 ( 2 R 0 6 r 1 ) \dfrac{d^2V_{1}}{dr_{1}^2} = \dfrac{H_{0} \pi}{R_{0}} * (2R_{0} - 6r_{1}) and d 2 V 1 d r 1 2 r 1 = 2 R 0 3 = 2 H 0 π R 0 < 0 \dfrac{d^2V_{1}}{dr_{1}^2}|_{r_{1} = \frac{2R_{0}}{3}} = \dfrac{-2H_{0} \pi}{R_{0}} < 0 \implies we have a maximum at r 0 = 2 R 0 3 r_{0} = \dfrac{2R_{0}}{3}

and r 1 = 2 R 0 3 h 1 = H 0 3 \boxed{r_{1} = \dfrac{2R_{0}}{3} \implies h_{1} = \dfrac{H_{0}}{3}}

\implies

r 2 = 2 3 r 1 = ( 2 3 ) 2 R 0 , H 1 = H 0 h 1 = 2 3 H 0 h 2 = H 1 r 1 ( r 1 r 2 ) = 2 3 2 H 0 \boxed{r_{2} = \dfrac{2}{3} r_{1} = (\dfrac{2}{3})^2 R_{0}}, \:\ H_{1} = H_{0} - h_{1} = \dfrac{2}{3} H_{0} \implies \boxed{h_{2} = \dfrac{H_{1}}{r_{1}}(r_{1} - r_{2}) = \dfrac{2}{3^2} H_{0}}

r 3 = 2 3 r 2 = ( 2 3 ) 3 R 0 , H 2 = H 1 h 2 = ( 2 3 ) 2 H 0 h 3 = H 2 r 2 ( r 2 r 3 ) = 2 2 3 2 H 0 \implies\boxed{r_{3} = \dfrac{2}{3} r_{2} = (\dfrac{2}{3})^3 R_{0}}, \:\ H_{2} = H_{1} - h_{2} = (\dfrac{2}{3})^2 H_{0} \implies \boxed{h_{3} = \dfrac{H_{2}}{r_{2}}(r_{2} - r_{3}) = \dfrac{2^2}{3^2} H_{0}}

For n 1 r n = ( 2 3 ) n R 0 , H n 1 = ( 2 3 ) n 1 H 0 n \geq 1 \:\ \boxed{r_{n} = (\dfrac{2}{3})^n R_{0}}, \:\ H_{n - 1} = (\dfrac{2}{3})^{n - 1} H_{0} and h n = 1 3 ( 2 3 ) n 1 H 0 \boxed{h_{n} = \dfrac{1}{3}(\dfrac{2}{3})^{n - 1} H_{0}} and

n = 1 h n = H 0 3 n = 1 ( 2 3 ) n 1 = H 0 \sum_{n = 1}^{\infty} h_{n} = \dfrac{H_{0}}{3}\sum_{n = 1}^{\infty} (\dfrac{2}{3})^{n - 1} = H_{0}

V n = ( 3 2 ) ( 8 27 ) n V c o n e V = n = 1 V n = \implies V_{n} = (\dfrac{3}{2})(\dfrac{8}{27})^{n} V_{cone} \implies V = \sum_{n = 1}^{\infty} V_{n} = 3 2 V 0 n = 1 ( 8 27 ) n = 12 19 V c o n e \dfrac{3}{2}V_{0}\sum_{n = 1}^{\infty} (\dfrac{8}{27})^n = \dfrac{12}{19}V_{cone}

and,

V = V c o n e V = V c o n e ( 1 12 19 ) = 7 19 V c o n e V^{*} = V_{cone} - V = V_{cone}(1 - \dfrac{12}{19}) = \dfrac{7}{19}V_{cone} \implies V V c o n e = 7 19 = α β α + β = 26 \dfrac{V^{*}}{V_{cone}} = \dfrac{7}{19} = \dfrac{\alpha}{\beta} \implies \alpha + \beta\ = \boxed{26} .

improve more

improve more - 2 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...